Plant and Animal Reproductive Strategies: Lessons from Offspring Size and Number Tradeoffs - Dani, K. G. Srikanta; Kodandaramaiah, Ullasa (Frontiers in Ecology and Evolution, 2017)
The tradeoff between offspring size and number is ubiquitous and manifestly similar in plants and animals despite fundamental differences between the evolutionary histories of these two major life forms. Fecundity (offspring number) primarily affects parental fitness, while offspring size underpins the fitness of parents and offspring. We provide an overview of theoretical models dealing with offspring size and fitness relationships. We follow that with a detailed examination of life-history constraints and environmental effects on progeny size and number, separately in plants and animals. The emphasis is on seed plants, but we endeavour to also summarize information from distinct animal groups - insects, fishes, reptiles, birds, and mammals. Furthermore, we analyse genetic controls on progeny size and number in two model organisms - Arabidopsis and Drosophila. Despite the deep evolutionary divergence between plants and animals, we find four trends in reproductive strategy that are common to both lineages: (i) offspring size is generally less variable than offspring number, (ii) offspring size increases with increasing parent body size, (iii) maternal genes restrict offspring size and increase offspring numbers, while zygotic genes act to increase offspring size; such parent-offspring conflicts are enhanced when there is sibling rivalry, and (iv) variation in offspring size increases under sub-optimal (harsh) environmental conditions. The most salient difference between plants and animals is that the latter tend to produce larger (fewer) offspring under sub-optimal conditions while seed plants invest in smaller (many) seeds, suggesting that maternal genetic control over offspring size increases in plants but decreases in animals with parental care. The time is ripe for greater experimental exploration of genetic controls on reproductive allocation and parent-offspring conflicts in plants and animals under sub-optimal (harsh) environments.